Design of Power Monitoring System for 2 Solar Panels Based on Thingspeak - Hasanti, Widya Sukma; Mairizwan, M; Yulkifli, Y (PILLAR OF PHYSICS, 2024)
Indonesia is one of the countries with large solar energy potential, namely around 3,294.4 GW recorded in 2022. However, solar energy utilization during 2022 is only 0.01%. Based on this problem, a research was carried out which aimed to combine the power produced by solar panels. This research emerged as a response to the need for energy efficiency and desires. With proper monitoring, solar panel owners can optimize their use of solar energy, reduce waste, and ensure that their solar panels are working at maximum capacity. This research is included in engineering research to determine the performance specifications and design specifications of the system that has been designed. Performance specifications cover a series of system electronic components and monitoring data displays displayed on Thingspeak. The design specifications in this research include sensor characterization, accuracy and precision of the Power Monitoring System For 2 Solar Panels Based On Thingspeak. From the results of the design specifications, the sensor used in the system has a high linearity value, good accuracy of 98.735% (voltage), 97.027% (current), and 97.994% (light intensity) and good accuracy of 99.905% (voltage), 99.549% (current), and 99.874% (light intensity).